Waterwheel fin design and its efficiency for a diversion-based hydropower system in Malaysian rivers - Hazmin, Mohd Haniff; Mustapha, Faizal; Mohd Ariffin, Mohd Khairol Anuar; Abdul Halin, Izhal (Penerbit Universiti Malaysia Terengganu, 2016)
Hydropower has been utilized for decades in Malaysia, and has been known to be very reliable and a consistent source of green energy. There are several methods to generate hydropower, and this paper will touch on waterwheel driven diversion-based hydropower system. Waterwheel is a popular medium to convert the potential energy in river flows to kinetic energy. Many types of waterwheel designs had been developed over the years for a variety of purposes. This paper will discuss on the correlation between the types of waterwheel and its efficiency. Several designs of waterwheel is created with similar general parameters using computer aided drawing. The models are then analysed using a software for fluid analysis to see how the designs react under a certain condition. The result is translated and rearranged to compare of the efficiency of each design. From this research, the result can be used on future work involving hydropower systems using waterwheel as a driver for the generator. This research draws upon primarily on what design aspects will affect on the efficiency of the waterwheel itself and explore the limits of how much changes on the design parameters can be made until the efficiency reaches stagnancy. The conditions used in this research is created to be similar to that of the average condition in rivers in Malaysia.